CD44 receptor diversity and potential in preventative and regenerative therapies - Adam C. Midgley; Qiang Zhao (Clinical and Translational Discovery, 2022)
Abstract The cell‐surface receptor CD44 has collected a library of diverse functionalities represented across multiple facets of health and disease. Recent revelations by Kim et al. indicate the importance of CD44 and its interacting proteins in the governance over critical hepatocyte cell processes, which promote liver tissue regeneration. In this commentary, we discuss prospective solutions for targeting of CD44 via its variant isoforms to elicit therapeutic outcomes. We also provide examples of targeting and exploiting CD44 variant candidates, as well as their shared hyaluronan binding function, for the purpose of achieving preventative and regenerative therapies.